184quiz1solns

# 184quiz1solns - Math 184 Quiz 1 Solutions 1 f(x = Solution...

This preview shows page 1. Sign up to view the full content.

This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Math 184 Quiz 1 Solutions 1. f (x) = Solution: 2 f (x) = 3 (x3 - 11) 2 2 f (x) = ( 2 (x3 - 11) 2 ) = 3 ((x3 - 11) 2 ) (by the Constant Multiple Rule) 3 1 1 1 2 x3 -11 . 3 Find f (3). = = 21 3 3 2 (x 21 3 3 2 (x - 11) - 11) -1 2 (x3 - 11) (by the Chain Rule) 3x2 = x2 (x3 - 11) = 9 16 -1 2 -1 2 = 2 x . x3 -11 So, f (3) = 2 3 33 -11 = 9. 4 2. g(x) = Solution: dg dx ( x+1)4 . ( x-1)3 Find dg dx . = d dx (x 2 +1)4 1 (x 2 1 -1)3 = 1 d 2 dx ((x d + 1)4 )(x 2 - 1)3 - (x 2 + 1)4 dx ((x 2 - 1)3 ) 1 1 1 [(x 2 - 1)3 ]2 1 1 1 by the Quotient Rule 1 = d d 4(x 2 + 1)3 dx (x 2 + 1)(x 2 - 1)3 - (x 2 + 1)4 3(x 2 - 1)2 dx (x 2 - 1) 1 1 1 1 (x 2 -1 )6 1 by the Chain Rule (x 2 -1 )6 (The previous line would be ok for your final answer, but I'll simplify a bit more) = x = -1 2 1 = 4(x 2 + 1)3 1 x 2 1 -1 2 (x 2 - 1)3 - (x 2 + 1)4 3(x 2 - 1)2 1 x 2 1 1 1 -1 2 2x -1 2 (x 2 + 1)3 (x 2 - 1)3 - 3 x 2 (x 2 -1 )6 1 1 1 1 1 -1 2 (x 2 + 1)4 (x 2 - 1)2 x = 7 2 -1 2 1 1 (x 2 + 1)3 (x 2 - 1)2 2(x 2 - 1) - 3 (x 2 + 1) 2 (x 2 -1 )6 1 1 3 (x 2 + 1)3 2x 2 - 2 - 2 x 2 - 1 1 1 3 2 (x 2 -1 )4 ( x + 1)3 ( x - 7) 2 x( x - 1)4 1 x = -1 2 (x 2 + 1)3 1 1 1 1 2 2x - 7 2 (x 2 -1 )4 = 1 ( x x + 1)3 2x - ( x - 1)4 1 = ...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online